Rare immune diseases paving the road for genome editing-based precision medicine - Pavel-Dinu, Mara; Borna, Simon; Bacchetta, Rosa (Frontiers in Genome Editing, 2023)
Clustered regularly interspaced short palindromic repeats (CRISPR) genome editing platform heralds a new era of gene therapy. Innovative treatments for life-threatening monogenic diseases of the blood and immune system are transitioning from semi-random gene addition to precise modification of defective genes. As these therapies enter first-in-human clinical trials, their long-term safety and efficacy will inform the future generation of genome editing-based medicine. Here we discuss the significance of Inborn Errors of Immunity as disease prototypes for establishing and advancing precision medicine. We will review the feasibility of clustered regularly interspaced short palindromic repeats-based genome editing platforms to modify the DNA sequence of primary cells and describe two emerging genome editing approaches to treat RAG2 deficiency, a primary immunodeficiency, and FOXP3 deficiency, a primary immune regulatory disorder.